Case Report: A Case of Perifoveal Exudative Vascular Anomalous Complex With a Good Prognosis - Fu, Min; Hu, Pan; Zhang, Gang; Huang, Ludonghan; Xu, Huan; Huang, Ju; Wu, Meihui; Chen, Yanli (Frontiers in Medicine, 2021)
Significance: Perifoveal exudative vascular anomalous complex (PEVAC) is a unique clinical lesion. PEVAC manifests as isolated perifoveal vascular lesions, and it is easily misdiagnosed. Thus far, PEVAC case reports are rare. PEVAC is typically inconsistent with other reported macular lesions. Purpose: To report our 24-month follow-up experience of the treatment of PEVAC with a micropulse laser (MPL). Case report: A 56-year-old Chinese woman with no history of other diseases complained of decreased vision in her left eye that had persisted for more than one year. She underwent comprehensive ophthalmic examinations, including a vision test, slit lamp fundus exam, optical coherence tomography (OCT), optical coherence tomography angiography (OCT-A), fluorescein fundus angiography (FFA) and indocyanine green angiography (ICGA). Intravitreal injection of ranibizumab was ineffective, and bleeding, exudation and visual acuity were not improved. After two rounds of micropulse laser (MPL) treatment, the patient was followed up with, and the prognosis was good. Conclusion: Because PEVAC is very rare, there have been no randomized controlled trials evaluating treatment methods, and a standard treatment model is lacking. There is no clear risk score to predict the outcome of PEVAC, and early diagnosis is important because the lesions readily cause irreversible damage. Therefore, PEVAC patients must be treated in a timely and rapid manner. Our results indicate that MPL can be used as an alternative treatment for PEVAC patients.